Ethnomedicinal Use of Zingiberaceae by the Mentawai Community in Saumanganyak Village, West Sumatra, Indonesia - Linda Wiliana; Erismar Amri; Zikra (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
The Mentawai Islands, located west of mainland West Sumatra, are part of popp Sumatra Province. The Mentawai people are the indigenous people of the islands and are renowned for their traditional healing practices, practiced by the "gadai mulaggek" (sagei mulaggek). Few published studies on Mentawai plant medicine have been published, most of which indicate that Zingiberaceae is one of the most widely used families. This study examines the traditional knowledge of Zingiberaceae among the Mentawai people of Saumanagnyak Village. Shamans or "gadai mulaggek" were interviewed directlly to obtain firsthand information about treatments using plants from the Zingiberaceae family. This study indicates that six species of Zingiberaceae are used in traditional Mentawai medicine